Corporate taxation and firm-specific determinants of capital structure: Evidence from the UK and US multinational firms - Sarmad Ali; Adalberto Rangone; Muhammad Farooq (Journal of Risk and Financial Management, 2022)
This paper aims to examine whether effective tax rate and firm-specific factors (such as firm size, growth opportunities, tangibility, risk, profitability, non-debt tax shields and liquidity) impact the capital structure of multinational firms in the energy sector. We employ regression models consisting of OLS, fixed effect and random effect to test balanced panel dataset of multinational firms based in the UK and USA over the period 2011-2019. We show a positive and significant effect of tangibility, risk, profitability and non-debt tax shields on long-term and total debt measures of capital structure. In the case of short-term debt, however, we reveal that it is significantly negatively related to tangibility, non-debt tax shields and liquidity, and positively associated with firm risk. Moreover, we report that the effective tax rate and firm size are insignificantly negatively related to the leverage choices of multinational firms, and liquidity has a significant inverse relationship with long-term debt and total debt. This study reveals mixed support for the prevailing capital structure theories and evidence that multinational firms are unequivocally responsive to the capital structure. The results significantly contribute to evaluating multinational firms in the energy sector and show how managers can achieve an optimal level of capital structure.
Keywords: 330; capital structure; effective tax rate; firm-specific factors; multinational firms